The geochemical evaluation and biological effect of Aspergillus niger on the kerogen-bearing limestone of El Galala El Qebbliay plateau, Wadi Araba area, North Eastern Desert, Egypt - R.Sh. Mohareb; Nora Sh. Gad; Doaa A. Mousa (Egyptian Journal of Petroleum)
The dark grey limestone in El Galala El Qebbliay plateau, in North Eastern Desert, Egypt contains TOC (Total Organic Carbon) that ranges from 0.24 to 1.84 wt.% and reaches good organic richness, geochemical analysis made for the collected samples indicated that the samples have from poor to good organic richness, with poor hydrocarbon potentiality. The kerogen type is mainly type III, or III/IV with immature thermal maturation. The presence of uranium is useful as an acceleration mineral for hydrocarbon maturation. Recovery of metal sorbet into the biomass is one of the important aspects of any successful biosorbation process. Bioleaching is a new trend for leaching and processing operation of ground ore. Aspergillus niger is one of the most widely used fungi in the bioleaching applications and has many advantages over bacterial leaching. Uranium can be easily recovered by solvent extraction unit. This study shed the light to geochemical evaluation for the study area, important clean and environmental friendly source to collect the organic material. The action of A. niger resulted in devenish the uranium content of the limestone, and recollect it as a valuable ore.